2018
DOI: 10.1158/0008-5472.can-17-2615
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Urothelial Bladder Carcinoma via Microfluidic Immunoassay and Single-Cell DNA Copy-Number Alteration Analysis of Captured Urinary-Exfoliated Tumor Cells

Abstract: The increasing incidence of bladder cancer and its high rate of recurrence over a 5-year period necessitate the need for diagnosis and surveillance amelioration. Cystoscopy and urinary cytology are the current tools, and molecular techniques such as BTA stat, NMP22, survivin mRNA, and urovysion FISH have attracted attention; however, they suffer from insufficient sensitivity or specificity. We developed a novel microfluidic approach for harvesting intact urinary-exfoliated tumor cells (UETC), either individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Spiking experiments demonstrated that, using the UriChip, the CE of BC cells spiked in leukocytes and urine from healthy donors achieved 53%, typical for size-based filtration (53,54). Higher efficiencies have recently been reported by Cheng et al, using a size-based microfluidic system, but with less complex model samples, i.e., with BC cells diluted in PBS which do not fully represent the cellular heterogeneity of biological samples (33). Accordingly, cells with different sizes and morphologies were found to be retained in the UriChip, with those originating from BC patients exhibiting higher shape deformation capacity and squeezing though narrower gaps in comparison to similar sized urothelial cells from urine of healthy donors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Spiking experiments demonstrated that, using the UriChip, the CE of BC cells spiked in leukocytes and urine from healthy donors achieved 53%, typical for size-based filtration (53,54). Higher efficiencies have recently been reported by Cheng et al, using a size-based microfluidic system, but with less complex model samples, i.e., with BC cells diluted in PBS which do not fully represent the cellular heterogeneity of biological samples (33). Accordingly, cells with different sizes and morphologies were found to be retained in the UriChip, with those originating from BC patients exhibiting higher shape deformation capacity and squeezing though narrower gaps in comparison to similar sized urothelial cells from urine of healthy donors.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the prognostic significance of CTCs in BC, microfluidic analysis of putative cancer biomarkers in voided urine would be ideal, non-invasive and provide significant benefits for patient monitoring, particularly at early stages of the disease, when survival rates are higher and CTCs may not yet be present. Nevertheless, only a scarcity of studies have used microfluidic chips for urine-based BC detection, employing different detection principles, complex systems, and processing times (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…This antigen has been recognized as a human complement factor H-related protein (hCFHrp) and inhibits the complement pathway to cause cytolysis in cells with a resulting selective advantage for the tumour [7]. Previous studies have suggested that the sensitivity of the BTA stat test is superior to urine cytology, and it has been approved by the US Food and Drug Administration for diagnosing and monitoring of BC [8,9]. However, the speci city of the BTA stat test is often disturbed by some factors, such as infection and intravesical treatment [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The bladder tumour antigen (BTA) stat test is the most concerned BC marker detection method and it has been approved by the US Food and Drug Administration for diagnosing and monitoring of BC [7,8]. This antigen has been recognized as a human complement factor H-related protein (hCFHrp) and inhibits the complement pathway to cause cytolysis in cells with a resulting selective advantage for the tumour [9].…”
Section: Introductionmentioning
confidence: 99%